1991
DOI: 10.1021/la00060a039
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between hydrophobic surfaces. Dependence on temperature and alkyl chain length

Abstract: Attractive forces between two hydrophobized mica surfaces immersed in water were measured using the surface force apparatus (SFA) over the temperature range 25-50 °C. Monolayers of dihexadecyldimethylammonium (DHDA), dioctadecyldimethylammonium (DODA), or dieicosyldimethylammonium (DEDA) surfactants were deposited onto mica by dipping cleaved mica into a cyclohexane solution containing the surfactant. The SFA measurements confirm the presence of a very long range attractive force reported in previous studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 0 publications
5
89
2
Order By: Relevance
“…Seemingly contradictory data have been published concerning the effects of electrolyte ions (59,62,73,(78)(79)(80)(81) and temperature (82,83). Removal of dissolved gas, however, has been consistently shown to decrease the range of the attraction as well as its magnitude, but only at long range (81,(84)(85)(86)(87).…”
Section: Direct Measurement Of Forces Between Hydrophobic Surfacesmentioning
confidence: 99%
“…Seemingly contradictory data have been published concerning the effects of electrolyte ions (59,62,73,(78)(79)(80)(81) and temperature (82,83). Removal of dissolved gas, however, has been consistently shown to decrease the range of the attraction as well as its magnitude, but only at long range (81,(84)(85)(86)(87).…”
Section: Direct Measurement Of Forces Between Hydrophobic Surfacesmentioning
confidence: 99%
“…Experimental evidence of the long range attractions (e.g., 10-100 nm) between hydrophobic surfaces has been known for several years (16)(17)(18)(19)(20). Although the interpretation of the origin of the long range attraction has been somewhat controversial, this phenomenon has been attributed, at least in part, to a theoretically predicted cavitation between hydrophobic surfaces.…”
mentioning
confidence: 99%
“…There is evidence of preexisting bubbles 50-500 nm in diameter and 5-50 nm in height on some hydrophobic surfaces (mechanism iii), but these bubbles have only been detected by invasive techniques such as atomic force microscopy (AFM) imaging (10,(14)(15)(16)(17). Other AFM and surface forces apparatus studies have not reported seeing nanobubbles (19,20).…”
mentioning
confidence: 99%